Castor Plant (Ricinus communis L.) Leaf Extract as Potential Antibacterial Against The Growth of Mycobacterium Tuberculosis - Istaufa, Fikriaddin Syafiq; Subagio, Yoyok; Suswati, Irma; , Isbandiyah (Folia Medica Indonesiana, 2022)
Highlight : • Patients experiencing failure of first-line drug and developing multidrug resistant tuberculosis (MDR-TB) has increased throughout 2011-2015. • Castor plant leaf extract (Ricinus communis L.) has an antibacterial potential against the growth of Mycobacterium tuberculosis bacteria. Abstract: Mycobacterium tuberculosis is the cause of pulmonary tuberculosis that can reduce human health. In the therapy of the disease, patients can develop resistance to tuberculosis drugs. Based on the 2015 health profiles of Indonesia, 15,380 people were suspected to have multidrug-resistant tuberculosis (MDR-TB), while 1,860 people were confirmed patients with MDR-TB. There is a need for innovation to develop the latest treatments using natural ingredients, one of which is castor plant (Ricinus communis L.) that contains antibacterial compounds against Mycobacterium tuberculosis. This study aimed to understand the antimicrobial potential of castor plant (Ricinus communis L.) leaf extract against the growth of Mycobacterium tuberculosis. This scientific paper was a quantitative systematic review study. Literature in the form of journal articles and books were obtained through search engines, i.e. ebook database, Google Scholar, Cochrane, Wiley, and PubMed. The results of the literature source search were 19 journal articles and 4 ebooks, as well as 4 journal articles that were in accordance with the title of this literature review and discussed the effects of castor plants on the growth of Mycobacterium tuberculosis. The results of the analysis showed that castor plant (Ricinus communis L.) leaf extract has the potential in the antibacterial activity against the growth of Mycobacterium tuberculosis because it contains phytochemicals in the form of flavonoids, saponins, alkaloids, tannins, and fatty acid amides derived from ricinoleic acid as the main constituent of castor plants (Ricinus communis L.). There is antimicrobial potential for castor plant (Ricinus communis L.) leaf extract against the growth of Mycobacterium tuberculosis.